Accumulation of heptaprenyl diphosphate sensitizes Bacillus subtilis to bacitracin: implications for the mechanism of resistance mediated by the BceAB transporter. Issue 1 (23rd May 2014) - Kingston, Anthony W.; Zhao, Heng; Cook, Gregory M.; Helmann, John D.
Summary Heptaprenyl diphosphate (C35‐PP) is an isoprenoid intermediate in the synthesis of both menaquinone and the sesquarterpenoids. We demonstrate that inactivation of ytpB, encoding a C35‐PP utilizing enzyme required for sesquarterpenoid synthesis, leads to an increased sensitivity to bacitracin, an antibiotic that binds undecaprenyl pyrophosphate (C55‐PP), a key intermediate in cell wall synthesis. Genetic studies indicate that bacitracin sensitivity is due to accumulation of C35‐PP, rather than the absence of sesquarterpenoids. Sensitivity is accentuated in a ytpB menA double mutant, lacking both known C35‐PP consuming enzymes, and in a ytpB strain overexpressing the HepST enzyme that synthesizes C35‐PP. Conversely, sensitivity in the ytpB background is suppressed by mutation of hepT or by supplementation with 1, 4‐dihydroxy‐2‐naphthoate, a co‐substrate with C35‐PP for MenA. Bacitracin sensitivity results from impairment of the BceAB and BcrC resistance mechanisms by C35‐PP: in a bceAB bcrC double mutant disruption of ytpB no longer increases bacitracin sensitivity. These results suggest that C35‐PP inhibits both BcrC (a C55‐PP phosphatase) and BceAB (an ABC transporter that confers bacitracin resistance). These findings lead to a model in which BceAB protects against bacitracin by transfer of the target, C55‐PP, rather than the antibiotic across the membrane.